Rapid PCR identification of Prevotella copri in an Australian cohort of pregnant women. (17th June 2020) - Gray, Lawrence; Hasebe, Kyoko; O'Hely, Martin; Ponsonby, Anne-Louise; Vuillermin, Peter; Collier, Fiona; ,
Abstract: Gut bacteria from the genus Prevotella are found in high abundance in faeces of non-industrialised communities but low abundance in industrialised, Westernised communities. Prevotella copri is one of the principal Prevotella species within the human gut. As it has been associated with developmental health and disease states, we sought to (i) develop a real-time polymerase chain reaction (PCR) to rapidly determine P. copri abundance and (ii) investigate its abundance in a large group of Australian pregnant mothers. The Barwon Infant Study is a pre-birth cohort study ( n = 1074). Faecal samples were collected from mothers at 36 weeks gestation. Primers with a probe specific to the V3 region of P. copri 16S rRNA gene were designed and optimised for real-time PCR. Universal 16S rRNA gene primers amplified pan-bacterial DNA in parallel. Relative abundance of P. copri was calculated using a 2 -Δ Ct method. Relative abundance of P. copri by PCR was observed in 165/605 (27.3%) women. The distribution was distinctly bimodal, defining women with substantial ( n = 115/165, 69.7%) versus very low P. copri expression ( n = 50/165, 30.3%). In addition, abundance of P. copri by PCR correlated with 16S rRNA gene MiSeq sequencing data ( r 2 = 0.67, P < 0.0001, n = 61). We have developed a rapid and cost-effective technique for identifying the relative abundance of P. copri using real-time PCR. The expression of P. copri was evident in only a quarter of the mothers, and either at substantial or very low levels. PCR detection of P. copri may facilitate assessment of this species in large, longitudinal studies across multiple populations and in various clinical settings.